Determination of knowledge and health literacy among women with type 2 diabetes in teaching hospitals of TUMS - A Tol; A Pourreza; E Tavasoli; A Rahimi Foroshani (Tehran University of Medical Sciences, 2012)
Background: Health literacy is the degree to which individuals have the capacity to obtain, process, and understanding basic health information and services needed to make appropriate health decisions. The aim of this study was to assess relationship between health literacy and knowledge of women with type 2 diabetes. Materials & Methods: In this cross sectional survey, 160 women with type 2 diabetes were selected by convenience sampling method. Data collected by using a STOHFLA standard questionnaire and knowledge was measured by self-administrated questionnaire. Obtained data analyzed by SPSS16 software in two categories of descriptive and inferential statistics (Chi-square and Pearson coefficient). Results: The mean age of studied population was 52.73±8.56 years old. The means of health literacy and knowledge was 40.57±15.87 and 21.52±2.94, respectively. There was a relation between occupation, education and family history with knowledge and health literacy score, and also between incomes with knowledge. There was reverse significant relation between age and disease duration with knowledge and health literacy. Conclusion: Results indicated that patients did not have the appropriate knowledge in type 2 diabetes, as well as health literacy which was also moderate. These results confirmed the need to develop of education for improving and increasing the appropriate knowledge and health literacy among studied women.